The Black Box Testing of the "Hybrid Engine" Application Using Boundary Value Analysis Technique: - - Megawati, Citra Dewi; Miwa, Nina Deskartika; Palevi, Bima Romadhon Parada Dian (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The "Hybrid Engine" application is an introduction to a hybrid engine that is packaged attractively and can be accessed online, this application is very important for conveying information about hybrid engines, if an error occurs in the functional application there can be misunderstandings about the information conveyed. Therefore it is necessary to test to ensure the quality of the application that has been produced. Testing is an evaluation process of assessing the functional quality of software to check whether the software meets the expected process or not. Functional processes that have not been maximized can cause inequalities in the data information to be displayed. Applications that have been designed must go through the testing stages to ensure the level of functional quality. Of the several types of black box testing methods, one of them is Boundary Value Analysis. The method tests the maximum and minimum number of digits to produce a valid value and is easy enough to test "hybrid engine" applications. The first stage carried out in this research is to identify the functionality to be processed and ensure that the maximum and minimum number of digits matches the predetermined system arrangement. The result of applying the method used is that the quality of the application is under its function, and can be utilized properly by the user. The results of the Boundary Value Analysis test show that the application is following the expected system and instructions with a success percentage of  78.245615%.